Safe spaces or a pedagogy of discomfort? Senior high-school teachers' meta-emotion philosophies and climate change education. Issue 1 (14th February 2021) - Ojala, Maria
Abstract: The aim of this study is to explore senior high-school teachers' beliefs about the role of emotions in climate change education and their perception of how they deal with emotional reactions in the classroom. The theoretical framework consists of meta-emotion philosophies, teachers' beliefs, and critical emotion theories. Sixteen Swedish teachers were interviewed. Four overarching emotion beliefs were identified: a disapproving view, a danger-oriented view, a partial acceptance view, and a complexity view. Four overarching coaching themes were found: avoidance, action-based and reappraisal-based coaching, strategies to approach negative emotions, and flexibility and adjustment-based coaching. Implications for teacher education are discussed. Supplemental data for this article is available online at https://doi.org/10.1080/00958964.2020.1845589 .